SISTEM INFORMASI MANAJEMEN MASJID BERBASIS WEBSITE (STUDI KASUS : MASJID BAITUL IKHWAN) - Eka Budhy P; Rita Dewi; Hilal Fajri Negara (Fakultas Teknik Universitas Persada Indonesia YAI, 2021)
The mosque is a place to worship or worship Allah SWT. The function of the mosque is not only as aplace to pray but also as a means of developing Islamic insight. As for one of the problems in the mosque which is known to not have an information system to process activity data, Friday prayer schedules, hallrentals, good and efficient finances at the Baitul Ikhwan Mosque. Based on the problemsdescribed, amosque information system is needed and a Website-Based Mosque Management Information System is needed using the waterfall method. The system tools used include the Unified Modeling Language (UML) such as use cases and activity diagrams, Entity Relationship Diagrams (ERD), and Hierarchy plus Input Process Output (HIPO). Which serves to make it easier for mosque administrators to carry out their duties from adding data, changing data, and deleting data that is no longer used or can print and then save in a computer system. And with this website, it is easier for the public to find information on mosquemanagement, and for mosque administrators it is easier to makea data recapitulation by printing it as a softcopy in pdf form and it will not be difficult to find the data file again in the system when it is printed. The information system built is website-based using a programming language, namely Hypertext Preprocessor (PHP).